Challenges Associated with Menstrual Hygiene among Adolescent Girls Attending Bocharia Primary School in Nyamira County, Kenya - Manyara, Martha Bosibori; Okube, Okubatsion Tekeste (Open Journal of Obstetrics and Gynecology, 2023)
Abstract Background: Approximately, half a million of adolescent girls in the world feel frustrated during their monthly period due to poor menstrual hygiene practices. In the low-and-middle income countries, about three-quarters of girls do not have access to clean sanitary materials, and use low-quality products. In the Sub-Saharan African countries, menstruation among school age girls is a neglected issue. Poor menstrual hygiene practices expose adoles cent girls to reproductive organ infections, psychosocial stress, and poor school attendance. However, the available data concerning challenges asso ciated with menstrual hygiene among school girls in the remote areas of Kenya remains unknown. Aim: To assess challenges associated with men strual hygiene among adolescent girls attending Bocharia Primary School in Nyamira County, Kenya. Methods: The target population was grade 4 to 8 adolescent girls (n = 111) aged 10 - 19 years. Hence, census method of sam pling was used to include all the girls in grade 4 - 8. Raw data was obtained using a Semi-structured questionnaire which was tested by a representation of 11 girls (10% of the sample size) who had the same characteristics. Data was analyzed using SPSS version 21 with both descriptive and inferential sta tistics. In descriptive statistics, frequency and percentage were generated. The chi-square test of independence was used to determine associations between some socio-demographic variables of the girls and menstrual hygiene prac tice. A p-value of less than 0.05 was considered to be significant. Results: The study found that majority (57%) of the respondents had poor menstrual hy giene practices associated with lack of accessibility and affordability to sani tary products, functional and safe latrines, shortage of soap and water supply, and sanitation facilities. Approximately half (47.8%) of the respondents re ported that menstrual hygiene practices are highly influenced by taboo from cultural beliefs and societal norms. Girls who live with both parents were more likely (73.3%) to wash their body with water and soap during monthly bleeding as compared to those girls from single mother (64.7%) and those who live or grand Mothers (42.9%). The toilets or latrines that were allocated to the girls were unlockable, which threatens privacy and safety of the girls. Conclusions: Most of the school girls had poor menstrual hygiene practices associated with lack of sanitary products, safe and functional latrines, ade quate water supply, soaps and sanitation facilities. Adequate attention to menstrual hygiene management should be given by the water, sanitation, and hygiene (WASH) program, education sectors, and sexual and reproductive health programs.
Copyright © 2023 by author(s) and Scientific Research Publishing Inc. This work is licensed under the Creative Commons Attribution International License (CC BY 4.0).
Keywords: Kenya; Menstrual Hygiene; Menstrual Hygiene Practices